Study of demography and clinical profile of ectopic pregnancies in a tertiary level hospital in Uttarakhand: a five year review - Nimonkar, Shweta; Chaudhari, Priyanka; Saxena, Namrata; Gupta, Vineeta; Tandon, Archna; Singh, Parul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Ectopic pregnancy is a condition when a fertilized ovum is implanted outside the uterine cavity. Life threatening risk of rupture of ectopic pregnancy remains one of the important causes of maternal mortality in India. The aim of study is to analyse the clinical profile, associated risk factors, complications, treatment outcomes to improve maternal mortality and morbidity associated with ectopic pregnancy. Methods: It is a retrospective study conducted at Shri Guru Ram Rai Institute of Medical and Health Sciences from January 2015 to January 2020. A total of 182 patients diagnosed of Ectopic Pregnancy were analysed for clinical profile, risk factors, serology, ultrasound findings, complications, treatment offered and outcome. Results: During the study period of 5 years there were total 182 patients who were diagnosed of ectopic pregnancy showing the incidence of ectopic pregnancy in our hospital 1.4% of total number of deliveries. Majority of patients were in the age group of 25 to 30 years (43.95%). Mostly multiparous women (80.1%) had ectopic pregnancy. Majority of patients (56.1%) had no associated risk factors for ectopic pregnancy. Main presenting complain was abdominal pain in 58.8% of patients. Majority of patients (63.2%) had surgery as primary care which indicates delay in diagnosis and arrival at hospital especially in hilly region of Uttarakhand. Conclusions: Ectopic pregnancies need to be diagnosed timely to decrease maternal morbidities and mortalities. Clinical signs and symptoms with serology (Serum beta hCG) and radiological findings helps to optimize treatment for potentially life-threatening condition.